A Review of the Unemployment - Economic Growth Nexus in Nigeria from 1980 to 2015: A Disaggregated Approach - Olaniyi, Oyinlola; Ali, Muhammad; Moses, Adesanya Babatunde (Growth, 2021)
The phenomenon of jobless growth in Nigeria in recent years has called to question the Okun’s law that the growth of gross domestic product (GDP) reduces unemployment. This study therefore, analyses the nexus between GDP growth and unemployment in Nigeria by disaggregating total output into its sectoral components to analyze the impact of sectoral output on unemployment using data from 1980 to-2015 employing the econometric technique of Autoregressive Distributed Lag (ARDL) bound testing approach. Two ARDL models were specified. The first bound test revealed the existence of co integration between unemployment and GDP growth. The growth of GDP is positively related to unemployment in the long run but a negative relationship was found in the short run. The result of the disaggregated model (i.e the second ARDL model) found no long run relationship between unemployment and agriculture, industry, construction, trade, and services. We opined that the findings of the disaggregated model resulted from the disconnection between aggregate demand and aggregate supply of the productive sectors and the lack of direct linkages between the oil sector and other sectors of the economy. The study recommends that such linkages should be forged through enhanced funding of research and development, technological innovation and the development of value chain of agriculture and solid minerals output. Nigerians should be encouraged to consume locally made products. Efforts should be intensified to develop direct linkages between the oil sector and other sectors through input supply contracts and the development of downstream industries in the oil sector.